PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. TRUST BONTANG - Azis, Boy Anggriawan (EKONOMIA, 2019)
Boy Anggriawan, 2018. Faculty Of Economics, University August, 1945 Samarinda. Do working safety and health of activity have an effect on positif and significant to employees performance at PT. TRUST in Bontang. Under the guidance of Mrs. Elfreda Aplonia Lau as counselor I and Mrs. Rina Masitoh as counselor II. Theory base which used in this research is Management Operational where explaining to regardin safety of work and of health of activity and also employees performance. As for this research hypothesis is working safety and health of activity have an effect on positif and significant to employees performance at PT. TRUST in Bontang. Method Research by using kuesioner with scale of likert. Research population is entire/all employees of PT. TRUST and of sampel research counted 80 employees people with technique intake of sampel that is sampling purposive. Analyzer the used doubled linear regresi which where beforehand have to test classic assumption. Pursuant to result of solution and research hence there is positive influence and significant between working safety to employees performance at PT. TRUST in Bontang. This Matter because of working safety very is influencing of performance, work of field progressively heavily with big equipments, wheater condition which uncertain, so that company have to pay attention prima facie safety storey;level to be accident of activity not happened. There is positive influence but not significant between health of activity to employees performance at PT. TRUST in Bontang